Free-list Measures of Cognitive Sharing and Organization: Ethnobotany in Rural Missouri. Issue 2 (May 2019) - Robbins, Michael C.; Nolan, Justin M.
We present a normed measure of cognitive sharing/diversity and a measure of cognitive organization that can be derived from free lists. They are useful for making cross-cultural and intracultural comparisons both within and between culturally constituted cognitive domains. An ethnographic example using data collected in rural Missouri from 40 novice and expert respondents to the domain of wild plants is used for illustrative purposes. Consistent with previous results, experts exhibit more cognitive sharing, and a higher quantity of cognitive organization, than novices.